ANALISIS PEMELIHARAAN KOREKTIF PADA ALAT HFNC (High Flow Nasal Cannula) - Mukhlis, Alfi; Dabukke, Hotromasari; Ulina, Sri; Sijabat, Salomo (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2024)
Ventilator is a mechanical assistive device that functions to provide artificial respiration to patients by providing negative or positive air pressure to the lungs through the airways. who can maintain ventilation and administration of oxygen for long periods of time (Brunner and Suddarth, 2001). While the HFNC (High Flow Nasal Cannula) Ventilator is a Ventilator specifically used for the treatment of patients suffering from acute hypoxemia. It is necessary to carry out maintenance so that the tools with this type of research are of high quality The measurement result is the oxygen gas flow rate, according to the size of the flowrate selection, namely 30 lpm, 45 lpm and 60 lpm.